Seleção de bactérias lácticas com potencial probiótico provenientes de queijo colonial - André, Juliana Alexsandra Machado (2020)
Artisanal cheeses, also known as colonial cheeses, are commonly produced in the Southwest region of Paraná and their production techniques are transmitted verbally and passed down from generation to generation, as well as presenting a diverse microbial population, both desirable and undesirable bacteria, which can deteriorate the product and cause damage to the health of the consumer. Among the desirable microorganisms are the lactic acid bacteria, which are useful in the fermentation and cheeses preservation processes, in addition to having probiotic potential, since they can resist the acid pH of the stomach, gastric juice, bile salts and digestive enzymes, acting beneficially in the intestine. Among the many benefits that lactic acid bacteria provide for human health are antimicrobial, antioxidant and anticarcinogenic actions, as well as reducing the occurrence of intestinal diseases and lactose intolerance. In this context, the aim of the present study was to isolate and identify, through phenotypic analyses, lactic acid bacteria with probiotic potential from colonial cheeses. For that, samples of colonial cheese samples (n = 10) were used to the isolate of bacterial cultures. The bacteria were phenotypically characterized and tested for resistance to different temperatures, carbohydrate fermentation capacity and growth capacity at different NaCl concentrations. Subsequently, 20 isolates were selected for analysis of antimicrobial activity and susceptibility, tolerance, and resistance to acidic media. It was observed that most bacteria presented Gram-positive bacilli and negative catalase, all showed growth at the temperatures evaluated (10°C and 45°C) and most fermented all carbohydrates (glucose, lactose, sorbitol and mannitol) with gas production, characterized as heterofermentative. Regarding resistance to different antimicrobials, 75% were resistant to two or more antimicrobials. The isolates were also showed little sensitivity to the acidic medium, with longer survival time when the acidic medium was associated with milk and excellent resistance under intestinal conditions. The identification of microorganisms by MALDI-TOF identified five isolates as Lactobacillus brevis, two as Enterococcus faecium, three as Pediococcus acidilactici and one as Lactobacillus rhamnosus. Considering this context, it is possible to infer that the BAL present in the colonial cheeses analyzed have probiotic potential, deserving prominence in future research, since they have positive aspects in relation to the items evaluated.